West Bank and Gaza : Report to the AD HOC Liaison Committee. (IMF Staff Country Reports; Country Report, 2022)
The Palestinian economy is facing formidable challenges. The fiscal situation, high political, security and social tensions, rising inflation, movement and access restrictions and an unfinished structural agenda all weigh on the medium-term outlook. Under unchanged policies, debt is unsustainable and per capita GDP is projected to decline. The situation is particularly dire in Gaza with persistently high unemployment and poverty.